PENGARUH PENGGUNAAN KOLEKTOR PLAT DATAR PADA PENGERING PADI TIPE DRUM DRYER - Nur Hidayati; Iskandar Ridwan (Department of Mechanical Engineering, Universitas Andalas, 2019)
Rice is one of food items consumed by most Indonesian people. Rice quality is a matter that must be considered in rice production. Rice quality can be improved by proper post-harvest handling, one of which is the drying process. The drying process can be done by drying under the sunshine and drying by using a dryer. Drying under the sunshine takes a long time, is difficult to control, depends on the weather, is easily contaminated and requires a large place. To overcome this problem, a dryer is needed. The dryer used is the drum dryer type. This drum dryer also utilizes mechanical energy from the gasoline engine so that it can rotate the drum. On the inner surface of the drum, stirring blades are installed. This dryer also uses heat coming from internal channel wall solar collectors. In this experiment was carried out with 4 free variations, namely: motor rotation, air flow velocity, intensity of solar radiation and cycle time. Three or four data are taken from each variation. When the experiment is taking place, varied parameters and planned parameters such as temperature absorber, ambient temperature, collector outlet air temperature and drying chamber temperature are measured. And at the final of the experiment for each variation, final mass of dried rice are measured. From the result of research, it can be concluded that the optimum rice mass reduction rate was obtained for each variation, namely at 905.1 rpm motor rotation, 10 m/s air flow rate, 948 W/m2 intensity of solar radiation and 30 minutes rotation time.